2020
DOI: 10.1088/1361-665x/ab9ddb
|View full text |Cite
|
Sign up to set email alerts
|

A piezoelectric beam model with geometric, material and damping nonlinearities for energy harvesting

Abstract: To predict electrical generation in piezoelectric small-scale beam energy harvesting devices, it is important to have a complete mathematical model that captures the different associated phenomena. In the literature, some authors propose several alternatives of nonlinear mathematical formulations, with non-linearities coming from different physical aspects. All these formulations present good aptitudes to predict the nonlinear behavior of the system under different values of accelerations, geometry and boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Unlike the polynomial model proposed by Wagner and Hagedorn (2002), the nonlinear terms of the enthalpy density based on the ferroelastic hysteresis are dependent on the absolute value (or the signum function) of the strain, which is characterized by the hysteresis loop. Recent studies of a multimodal PVEH (Machado et al, 2020), a PVEH with segmented electrodes (Hu et al, 2021) connected to a single resistive circuit, and a PVEH connected to a diode bridge rectifier circuit (Leadenham and Erturk, 2020) validated the model proposed by Leadenham and Erturk (2015) by replicating the experimental results well. In addition to nonlinear stiffness softening, some studies also reported the importance of including nonlinear damping in the modeling process to explain the experimentally observed result that the displacement magnitude decreased when the excitation level increased.…”
Section: Introductionmentioning
confidence: 89%
“…Unlike the polynomial model proposed by Wagner and Hagedorn (2002), the nonlinear terms of the enthalpy density based on the ferroelastic hysteresis are dependent on the absolute value (or the signum function) of the strain, which is characterized by the hysteresis loop. Recent studies of a multimodal PVEH (Machado et al, 2020), a PVEH with segmented electrodes (Hu et al, 2021) connected to a single resistive circuit, and a PVEH connected to a diode bridge rectifier circuit (Leadenham and Erturk, 2020) validated the model proposed by Leadenham and Erturk (2015) by replicating the experimental results well. In addition to nonlinear stiffness softening, some studies also reported the importance of including nonlinear damping in the modeling process to explain the experimentally observed result that the displacement magnitude decreased when the excitation level increased.…”
Section: Introductionmentioning
confidence: 89%
“…Shahruz [ 7 ] arranged cantilever beam arrays with different resonant frequencies: research shows that under the action of external excitation, only one cantilever beam can match the vibration frequency of the environment, so the energy collection efficiency is low. In order to improve the energy harvesting efficiency of piezoelectric energy harvesters, researchers have carried out a lot of research on the introduction of nonlinear methods to broaden the working frequency band of energy harvesters [ 8 , 9 , 10 , 11 ]. Wang [ 12 ] proposed a cantilever beam with variable section thickness and established its distributed parameter model.…”
Section: Introductionmentioning
confidence: 99%
“…A prismatic beam with a rectangular cross-section is one commonly used mechanical structure of the harvester. The beam, which is constructed from a carrying substrate and a piezoelectric material, is applied for energy harvesting from various processes: mechanical vibration [1,2], rotational motion [3,4] and wind energy [5,6]. Mechanical energy is converted into electric energy in a piezoelectric material, which is squeezed or stretched during beam bending.…”
Section: Introductionmentioning
confidence: 99%
“…A carrying substrate is made from steel, brass, aluminum, copper or various composites. Ceramics, e.g., lead titanate zirconate [4,5]; composites made from piezoelectric ceramics and polymer matrix, e.g., Macro Fiber Composite [1,2]; and piezoelectric polymers, e.g., polyvinylidene fluoride [7], are the typical piezoelectric material used in beam manufacturing. Composites have lower efficiency in energy conversion than piezoelectric ceramics, but are more resistant than monolithic ceramic to destruction due to deformations [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation